Description of a new water mite of the genus Utaxatax (Acari, Hydrachnidia: Anisitsiellidae) from Kazakhstan - Tuzovskij, Petr V. (Zootaxa, 2020)
A new species of the genus Utaxatax (s.s.), U. stolbovi n. sp., is described from theAksu-Zhabagly Nature Reserve in the Republic of Kazakhstan. It is most similar to the Himalayan U. brahmeri Panesar, 2004. Similarities and morphological differences are discussed.